Does climate-smart agriculture technology improve farmers' subjective well-being? Micro-level evidence from Odisha, India - Dukhabandhu Sahoo; Pritisudha Mohanty; Surbhi Mishra; Manash Kumar Behera; Souryabrata Mohapatra (Farming System)
Since the global population is expected to reach 9.7 billion by 2050, food production must increase by 70% in the next 30 years to provide food security in the face of climate change. Implementing climate-smart agriculture technology (CSAT) is essential for ensuring food security and promoting economic growth in the context of sustainable agriculture. Climate change and weather patterns significantly affect agricultural yield, necessitating the implementation of more efficient, productive, and climate-resilient techniques. However, the use of CSAT is a behavioural decision that affects the subjective well-being of the users. Using smart agricultural practices reduces climate change's impact on agricultural productivity and promotes sustainable agriculture, improving adopters' welfare. This study examines how the use of CSAT affects rural households' subjective well-being in Odisha, India. The result of the study shows that the use of CSAT significantly affects the subjective well-being of the farmers. The measured impact is 0.149, 0.181, and 0.144 for farmers whose intensity is 0.251–0.500, 0.501–0.750, and 0.751 and above, respectively, as compared to farmers whose intensity is 0.0–0.250. This implies greater satisfaction for farmers who engage in the moderate use of CSAT practices. Low utilization of technology may not yield benefits for farmers, while the adoption of advanced technology may not be economically viable. Additionally, CSAT is not easily available to households residing in low-lying areas, preventing them from improving their well-being. Only a small number of landowners in impoverished areas utilize CSAT. Therefore, it is necessary to evaluate government regulations regarding land and tenancy as well as develop measures for farmers to adapt to new technologies.